PARADOKS TRITUNGGAL:: SEBUAH TINJAUAN LOGIS TENTANG TIGA DALAM SATU - Munthe, Denyka; Sumampouw, Alexander (STT-RAI Batam, 2025)
The doctrine of the Trinity is one of the most fundamental teachings in Christianity, but also the most difficult to understand rationally. How can the One God be simultaneously three persons: Father, Son, and Holy Spirit? This question has been a long debate, both among philosophers, theologians, and critics of other religions. At first glance, this concept seems to contradict the law of non-contradiction in classical logic, which states that something cannot be